Preparation method and application of electrochemical immunosensor for leather cultural relic detection

Through the preparation of sandwich electrochemical immunosensors, the CdS@Fe3O4 and Au NPs assembly platform is used, combined with magnetic glass carbon electrodes, the problem of low sensitivity of degraded leather cultural relics is solved, and the high sensitivity detection of collagen is achieved. A new method for detecting leather cultural relics.

CN119199095AActive Publication Date: 2024-12-27ZHEJIANG SCI-TECH UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411444925.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2024-12-27
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

It is difficult for the prior art to accurately identify degraded ancient leather cultural relics. Conventional detection methods have low sensitivity and cannot effectively distinguish different leather cultural relics. There is a problem of non-destructive detection of precious cultural relics.

Method used

Sandwich electrochemical immunosensor is used to form an Au/CdS@Fe3O4 signal amplification platform through the assembly of CdS@Fe3O4 and Au NPs. Combined with magnetic glassy carbon electrodes, qualitative detection of collagen is achieved, and the sensitivity and specificity of the detection are improved.

Benefits of technology

The ultra-sensitive identification of collagen is achieved, with a detection limit of 0.03pg/mL, which has good stability and repeatability, a wide detection range, and significantly improves the accuracy and efficiency of leather cultural relics detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005087470410000111
    Figure BDA0005087470410000111
Patent Text Reader

Abstract

The invention relates to the technical field of immunosensors, and discloses a preparation method and application of an electrochemical immunosensor for detecting leather cultural relics, and the preparation method comprises the following steps: (1) preparing CdS-Fe3O4; (2) preparation of Au / CdS coated Fe3O4; (3) preparation of Ab2-Au / CdS-coated Fe3O4: adding Au / CdS-coated Fe3O4 into a PBS (Phosphate Buffer Solution) containing Ab2 and BSA (Bovine Serum Albumin), and incubating; (4) preparation of a PEC immunosensor: dropping the Ab1 solution into a microwell plate, and incubating; dropping the BSA solution into the microwell plate; the collagen antigen is dropped into the microwell plate; the Ab2-Au / CdS coated Fe3O4 solution is dropped into a microwell plate, and the electrochemical immunosensor is obtained. The sandwich type photoelectrochemical immunosensor prepared by the invention can be used for simple, rapid, high-sensitivity and specific detection of collagen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of immunosensors, and more specifically relates to a preparation method and application of an electrochemical immunosensor for leather cultural relic detection. Background Art

[0002] In recent years, archaeologists have discovered a large number of leather products in tombs during archaeological excavations. As an organic polymer material, leather artifacts often suffer from severe degradation of collagen under the influence of the environment after thousands of years of baptism. Degraded leather artifacts have undergone tremendous changes in both appearance and internal structure, which makes it difficult to accurately identify the species of leather artifacts using some conventional detection methods, such as surface analysis, spectral analysis, and DNA analysis. In addition, due to the preciousness of artifacts, it is urgent to develop cross-validated non-destructive detection methods to identify the species of ancient leather artifacts.

[0003] The sandwich electrochemical immunosensor combines highly specific immunoassay technology with highly sensitive electrochemical analysis technology. It has the advantages of high sensitivity, simple preparation, rapid detection, low cost, etc., and has important application value in the field of clinical testing. Metal sulfide, as a widely used semiconductor material, has excellent physical and chemical stability and suitable band gap width, and is a very promising photoelectric active material. In particular, cadmium sulfide (CdS) has a strong light absorption ability in the visible light region. It is an extremely important photoelectric material and has attracted much attention due to its suitable band gap (2.2-2.4eV), excellent photocatalytic performance and unique structure. In recent years, gold nanoparticles (Au NPs) have been widely used in catalysis, optoelectronics, sensing and biomedicine due to their special physical and chemical properties and good biocompatibility. At the same time, due to the characteristics of accelerated electron transfer, excellent biocompatibility, conductivity and catalytic performance, gold nanoparticles have been widely used as substrate materials for electrochemical immunosensing analysis. In addition, cadmium sulfide (CdS) has also attracted widespread attention due to its large surface area, high electron mobility and relatively low toxicity, and has become a commonly used material in biological analysis. However, the electrochemical performance of a single nanomaterial is limited, and it is necessary to combine different nanomaterials according to their different characteristics to achieve better performance. Summary of the invention

[0004] The present invention aims to provide a method for preparing an electrochemical immunosensor for leather artifact detection, using Au / CdS@Fe3O4 assembled from CdS@Fe3O4 and Au NPs as a signal amplification platform to achieve qualitative detection of collagen. Due to the magnetic properties of Fe3O4, Au / CdS@Fe3O4 can be well attached to the surface of a magnetic glassy carbon electrode (MGCE). The resulting PEC immunosensor has good sensitivity, specificity, stability and repeatability. This strategy provides new ideas and potential approaches for the detection of a variety of leather artifacts.

[0005] In order to achieve the above object, the present invention is implemented by the following technical scheme: A method for preparing an electrochemical immunosensor for leather cultural relics detection comprises the following steps:

[0006] (1) Preparation of CdS@Fe3O4: Nanorod-shaped CdS was mixed with FeCl3·6H2O, sodium acetate, ethylenediamine, and ethylene glycol; the mixture was heated in a reactor for reaction, cooled naturally to room temperature, filtered, washed, and vacuum dried to obtain a CdS@Fe3O4 nanocomposite material;

[0007] (2) Preparation of Au / CdS@Fe3O4: CdS@Fe3O4 nanocomposite was dissolved in ultrapure water under ultrasonic wave, AuNPs solution was added and stirred, and then filtered, washed and vacuum dried to obtain Au / CdS@Fe3O4 nanocomposite;

[0008] (3) Preparation of Ab2-Au / CdS@Fe3O4: Au / CdS@Fe3O4 nanocomposites were ultrasonically dispersed in ultrapure water, and a PBS solution containing Ab2 and BSA was added. After incubation, an Ab2-Au / CdS@Fe3O4 solution was obtained and stored at 4°C.

[0009] (4) Preparation of PEC immunosensor: Ab1 solution was dropped into the microplate, and after incubation, the microplate was washed with PBS buffer; BSA solution was dropped into the microplate and washed with PBS buffer; collagen antigen was dropped into the microplate and washed with PBS buffer; finally, Ab2-Au / CdS@Fe3O4 solution was dropped into the microplate to obtain an electrochemical immunosensor.

[0010] The present invention uses a sandwich PEC immunosensor made of Au / CdS nanocomposite material with better detection performance than CdS to achieve ultra-sensitive identification of leather artifacts. - / h+ separation. Thereby increasing the photocurrent and realizing the amplification of the PEC immunosensor signal. In addition, Au nanoparticles (Au NPs) can accelerate the transfer of photogenerated electrons. Loading Au NPs on CdS@Fe3O4 (Au / CdS@Fe3O4) as a signal amplification not only combines their respective advantages, but also effectively separates electron holes, thereby improving the sensitivity of the PEC immunosensor. When Au NPs are modified on its surface, the conductivity of the material is enhanced and it has good biocompatibility. Most importantly, it provides sites for the loading of antibodies. Through the detection of collagen, the minimum detection limit was obtained to be 0.03pg mL. At the same time, compared with colloidal gold immunochromatography, time-resolved fluorescence immunochromatography, indirect enzyme-linked immunosorbent assay, etc., the sandwich PEC immunosensor shows better detection performance. Under visible light irradiation, the photocurrent signal of Au / CdS@Fe3O4 nanocomposite is 7 times that of CdS; under 808nm near-infrared light irradiation, the photocurrent signal of Au / CdS@Fe3O4 nanocomposite is 25 times that of CdS. The immunosensor has a good detection range (0.0001ng / mL~20ng / mL) and a low detection limit (0.03pg / mL). Under optimal conditions, the immunosensor has good stability, selectivity and repeatability.

[0011] Further preferably, the preparation of nanorod-shaped CdS in step (1) is prepared by a water bath method, wherein (CH3COO)2Cd and thiourea are added to ethylenediamine, stirred until completely dissolved, heated in a reactor for reaction, cooled, washed, and vacuum dried to obtain nanorod-shaped CdS.

[0012] Further preferably, the ratio of the added amounts of (CH3COO)2Cd, thiourea and ethylenediamine is 1.8-2.0g:1.2-1.5g:32mL; the stirring time is 0.5h-1h; the heating reaction is transferring the solution to a reactor and heating at 180-200°C for 12-24h; and the vacuum drying temperature is 40-60°C.

[0013] Further preferably, in step (1), the mixing ratio of nanorod-shaped CdS to FeCl3·6H2O, sodium acetate, ethylenediamine, and ethylene glycol is 0.2-0.4 g: 0.5-0.8 g: 1.5-1.8 g: 5-7 mL: 10-12 mL; the mass ratio of nanorod-shaped CdS to FeCl3·6H2O is 1: 1-3; the heating reaction in the reactor is to transfer the mixture to the reactor and heat it at 180-200° C. for 8-12 h;

[0014] Further preferably, in step (2), the preparation of Au NPs is as follows: the chloroauric acid solution is heated to boiling, and then a sodium citrate solution is added dropwise thereto, and the mixture is stirred evenly to obtain an Au NPs solution.

[0015] Further preferably, the concentration of the chloroauric acid solution is 0.8-1.2 mM; the concentration of the sodium citrate solution is 0.08-0.12 mM; and the stirring time is 10-20 min.

[0016] Further preferably, in step (2), the mixing ratio of CdS@Fe3O4 nanocomposite material and Au NPs solution is 0.5-0.8 g: 30-50 mL; and the stirring time is 10-12 h.

[0017] Further preferably, in step (3), the mixing ratio of Au / CdS@Fe3O4 nanocomposite material, ultrapure water and PBS solution containing Ab2 and BSA is 0.2-0.3 g: 0.5-0.6 mL: 0.5-0.8 mL; the concentration of Ab2 in the PBS solution containing Ab2 and BSA is 8-10 mg / mL, and the concentration of BSA is 0.8-1 wt%; the incubation is 24-30 h at 4 °C.

[0018] Further preferably, in step (4), the addition ratio of Ab1 solution, BSA solution, collagen antigen solution, and Ab2-Au / CdS@Fe3O4 solution is 80-100mL::100L:80-100mL; the concentration of Ab1 solution is 8-10g / mL, and the incubation is 0.5-1h; the concentration of BSA solution is 1-3wt%.

[0019] The second technical solution of the present invention: Application of the electrochemical immunosensor prepared by the above preparation method in the detection of leather cultural relics.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] (1) The sandwich-type photoelectrochemical immunosensor prepared by the present invention is used for the detection of collagen, has a short response time, a low detection limit, a wide linear range, and good stability, and can achieve simple, rapid, highly sensitive and specific detection, providing a new analytical method for the detection of leather artifact samples.

[0022] (2) The present invention increases the overall conductivity and reaction rate of the material by introducing gold nanoparticles.

[0023] (3) The electrode prepared by the present invention does not require the addition of any additional conductive agent or binder. Compared with traditional coating methods and mechanical methods such as roller pressing, the material loading is more uniform and effective, simpler, and has lower resistance.

[0024] (4) The materials used in the present invention have good biocompatibility, are green and pollution-free, have a simple preparation process, save time and effort, and the self-assembly process is easy to detect and modify. DETAILED DESCRIPTION

[0025] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0026] Example 1

[0027] (1) Preparation of Au NPs: Take 100 μL of chloroauric acid solution, heat it to boiling, and then add 10 μL of sodium citrate solution. The concentration of the chloroauric acid solution is 0.8 mM, and the concentration of the sodium citrate solution is 0.08 mM. Stir for 10 min to obtain a wine-red Au NPs solution.

[0028] (2) Preparation of CdS: 1.8 g (CH3COO)2Cd and 1.2 g thiourea were added to 32 mL ethylenediamine and stirred for 0.5 h. After complete dissolution, the solution was transferred to a Teflon-lined stainless steel autoclave and heated at 180°C for 12 h. The obtained precipitate was dried at 40°C in vacuum overnight to obtain nanorod CdS.

[0029] (3) Preparation of CdS@Fe3O4: 0.2 g of nanorod CdS, 0.5 g of FeCl3·6H2O, 1.5 g of sodium acetate, 5 mL of ethylenediamine, and 10 mL of ethylene glycol were mixed under vigorous stirring. The mixture was transferred to a Teflon-lined stainless steel autoclave and heated at 180°C for 8 h. The obtained precipitate was vacuum dried at 40°C for 8 h to obtain CdS@Fe3O4 powder.

[0030] (4) Preparation of Au / CdS@Fe3O4: 0.5 g CdS@Fe3O4 was dissolved in ultrapure water under ultrasound. After the solution was uniform, 30 mL of 0.8 mM AuNPs solution was added and stirred for 10 h. After the reaction was complete, the solution was washed with ultrapure water and vacuum dried overnight to obtain Au / CdS@Fe3O4 nanocomposite material.

[0031] (5) Preparation of Ab2-Au / CdS@Fe3O4: 0.2 g of Au / CdS@Fe3O4 nanocomposite was ultrasonically dispersed in 0.5 mL of ultrapure water. Then, 0.5 mL of PBS solution (pH 7.4) containing Ab2 (8 mg / mL) and BSA (0.8 wt%) was added to the above solution. After 24 h at 4°C, Ab2-Au / CdS@Fe3O4 solution was obtained and stored at 4°C.

[0032] (6) Preparation of PEC immunosensor: 80 μL of Ab1 solution (8 g / mL) was dripped into a 96-well microplate and incubated for 0.5 h to allow Ab1 to adsorb on the surface of the microplate. Then, the unbound portion of Ab1 was removed and the microplate was washed twice with PBS buffer (pH 7.4). Subsequently, 1 wt % and 200 μL of BSA solution were added to the microplate to block nonspecific binding sites. After washing three times with PBS buffer (pH 7.4), 100 μL of collagen antigens with concentrations of 1 mg / mL, 1 μg / mL, 1 ng / mL, and 1 pg / mL were injected into the microplate, respectively. After standing for 0.5 h, the plate was washed three times with PBS buffer (pH 7.4). Finally, 80 μL of Ab2-Au / CdS@Fe3O4 solution was dripped into the microplate to obtain an electrochemical immunosensor.

[0033] Example 2

[0034] (1) Preparation of Au NPs: Take 100 μL of chloroauric acid solution, heat it to boiling, and then add 10 μL of sodium citrate solution. The concentration of the chloroauric acid solution is 0.8 mM, and the concentration of the sodium citrate solution is 0.12 mM. Stir for 15 min to obtain a wine-red Au NPs solution.

[0035] (2) Preparation of CdS: Take 1.9 g (CH3COO )2 Cd and 1.4 g thiourea were added to 32 mL ethylenediamine and stirred for 1 h. After complete dissolution, the solution was transferred to a Teflon-lined stainless steel autoclave and heated at 190 °C for 24 h. The obtained precipitate was dried overnight in vacuum at 50 °C to obtain nanorod CdS.

[0036] (3) Preparation of CdS@Fe3O4: 0.3 g of nanorod CdS, 0.7 g of FeCl3·6H2O, 1.7 g of sodium acetate, 6 mL of ethylenediamine, and 11 mL of ethylene glycol were mixed under vigorous stirring. The mixture was transferred to a Teflon-lined stainless steel autoclave and heated at 190°C for 10 h. The obtained precipitate was vacuum dried at 50°C for 10 h to obtain CdS@Fe3O4 powder.

[0037] (4) Preparation of Au / CdS@Fe3O4: 0.7 g CdS@Fe3O4 was dissolved in ultrapure water under ultrasound. After the solution was uniform, 40 mL AuNPs solution was added and stirred for 11 h. After the reaction was complete, the mixture was washed with ultrapure water and vacuum dried overnight to obtain Au / CdS@Fe3O4 nanocomposite material.

[0038] (5) Preparation of Ab2-Au / CdS@Fe3O4: 0.25 g of Au / CdS@Fe3O4 nanocomposite was ultrasonically dispersed into 0.6 mL of ultrapure water. Then, 0.7 mL of PBS solution (pH 7.4) containing Ab2 (9 mg / mL) and BSA (0.9 wt%) was added to the above solution. After 24 h at 4°C, Ab2-Au / CdS@Fe3O4 solution was obtained and stored at 4°C.

[0039] (6) Preparation of PEC immunosensor: 80 μL of Ab1 solution (9 g / mL) was dripped into a 96-well microplate and incubated for 0.5 h to allow Ab1 to adsorb on the surface of the microplate. Then, the unbound portion of Ab1 was removed and the microplate was washed twice with PBS buffer (pH 7.4). Subsequently, 200 μL of 2wt% BSA solution was added to the microplate to block nonspecific binding sites. After washing three times with PBS buffer (pH 7.4), 100 μL of collagen antigens at concentrations of 1 mg / mL, 1 μg / mL, 1 ng / mL, and 1 pg / mL were injected into the microplate, respectively. After standing for 0.5 h, the plate was washed three times with PBS buffer (pH 7.4). Finally, 80 μL of Ab2-Au / CdS@Fe3O4 solution was dripped into the microplate to obtain an electrochemical immunosensor.

[0040] Example 3

[0041] (1) Preparation of Au NPs: Take 100 μL of chloroauric acid solution, heat it to boiling, and then add 10 μL of sodium citrate solution. The concentration of the chloroauric acid solution is 1.2 mM, and the concentration of the sodium citrate solution is 0.12 mM. Stir for 20 min to obtain a wine-red Au NPs solution.

[0042] (2) Preparation of CdS: Take 2.0 g (CH3COO )2 Cd and 1.5 g thiourea were added to 32 mL ethylenediamine and stirred for 1 h. After complete dissolution, the solution was transferred to a Teflon-lined stainless steel autoclave and heated at 200 °C for 24 h. The obtained precipitate was dried overnight in vacuum at 60 °C to obtain nanorod CdS.

[0043] (3) Preparation of CdS@Fe3O4: 0.4 g of nanorod CdS, 0.8 g of FeCl3·6H2O, 1.8 g of sodium acetate, 7 mL of ethylenediamine, and 12 mL of ethylene glycol were mixed under vigorous stirring. The mixture was transferred to a Teflon-lined stainless steel autoclave and heated at 200°C for 12 h. The obtained precipitate was vacuum dried at 60°C for 12 h to obtain CdS@Fe3O4 powder.

[0044] (4) Preparation of Au / CdS@Fe3O4: 0.8 g CdS@Fe3O4 was dissolved in ultrapure water under ultrasound. After the solution was uniform, 50 mL Au NPs solution was added and stirred for 12 h. After the reaction was complete, the solution was washed with ultrapure water and vacuum dried overnight to obtain Au / CdS@Fe3O4 nanocomposite material.

[0045] (5) Preparation of Ab2-Au / CdS@Fe3O4: 0.3 g of Au / CdS@Fe3O4 nanocomposite was ultrasonically dispersed into 0.6 mL of ultrapure water. Then, 0.8 mL of PBS solution (pH 7.4) containing Ab2 (10 mg / mL) and BSA (1 wt%) was added to the above solution. After 24 h at 4°C, an Ab2-Au / CdS@Fe3O4 solution was obtained and stored at 4°C.

[0046] (6) Preparation of PEC immunosensor: 100 μL of Ab1 solution (8 g / mL) was dropped into a 96-well microplate and incubated for 0.5 h to allow Ab1 to adsorb on the surface of the microplate. Then, the unbound portion of Ab1 was removed and the microplate was washed twice with PBS buffer (pH 7.4). Subsequently, 1 wt% 200 μL BSA solution was added to the microplate to block nonspecific binding sites. After washing three times with PBS buffer (pH 7.4), 100 μL of collagen antigens at concentrations of 1 mg / mL, 1 μg / mL, 1 ng / mL, and 1 pg / mL were injected into the microplate, respectively. After standing for 0.5 h, the plate was washed three times with PBS buffer (pH 7.4). Finally, 100 μL of Ab2-Au / CdS@Fe3O4 solution was dropped into the microplate to obtain an electrochemical immunosensor.

[0047] Example 4

[0048] (1) Preparation of Au NPs: Take 100 μL of chloroauric acid solution, heat it to boiling, and then add 10 μL of sodium citrate solution. The concentration of the chloroauric acid solution is 0.8 mM, and the concentration of the sodium citrate solution is 0.12 mM. Stir for 15 min to obtain a wine-red Au NPs solution.

[0049] (2) Preparation of CdS: Take 1.9 g (CH3COO )2 Cd and 1.4 g thiourea were added to 32 mL ethylenediamine and stirred for 1 h. After complete dissolution, the solution was transferred to a Teflon-lined stainless steel autoclave and heated at 190 °C for 24 h. The obtained precipitate was dried overnight in vacuum at 50 °C to obtain nanorod CdS.

[0050] (3) Preparation of CdS@Fe3O4: 0.5 g of nanorod CdS, 0.5 g of FeCl3·6H2O, 1.7 g of sodium acetate, 6 mL of ethylenediamine, and 11 mL of ethylene glycol were mixed under vigorous stirring. The mixture was transferred to a Teflon-lined stainless steel autoclave and heated at 190°C for 10 h. The obtained precipitate was vacuum dried at 50°C for 10 h to obtain CdS@Fe3O4 powder.

[0051] (4) Preparation of Au / CdS@Fe3O4: 0.7 g CdS@Fe3O4 was dissolved in ultrapure water under ultrasound. After the solution was uniform, 40 mL AuNPs solution was added and stirred for 11 h. After the reaction was complete, the mixture was washed with ultrapure water and vacuum dried overnight to obtain Au / CdS@Fe3O4 nanocomposite material.

[0052] (5) Preparation of Ab2-Au / CdS@Fe3O4: 0.25 g of Au / CdS@Fe3O4 nanocomposite was ultrasonically dispersed into 0.6 mL of ultrapure water. Then, 0.7 mL of PBS solution (pH 7.4) containing Ab2 (9 mg / mL) and BSA (0.9 wt%) was added to the above solution. After 24 h at 4°C, Ab2-Au / CdS@Fe3O4 solution was obtained and stored at 4°C.

[0053] (6) Preparation of PEC immunosensor: 80 μL of Ab1 solution (9 g / mL) was dripped into a 96-well microplate and incubated for 0.5 h to allow Ab1 to adsorb on the surface of the microplate. Then, the unbound portion of Ab1 was removed and the microplate was washed twice with PBS buffer (pH 7.4). Subsequently, 200 μL of 2wt% BSA solution was added to the microplate to block nonspecific binding sites. After washing three times with PBS buffer (pH 7.4), 100 μL of collagen antigens at concentrations of 1 mg / mL, 1 μg / mL, 1 ng / mL, and 1 pg / mL were injected into the microplate, respectively. After standing for 0.5 h, the plate was washed three times with PBS buffer (pH 7.4). Finally, 80 μL of Ab2-Au / CdS@Fe3O4 solution was dripped into the microplate to obtain an electrochemical immunosensor.

[0054] Example 5 (Detection of collagen in leather artifacts)

[0055] Step 1: Use an electrochemical workstation three-electrode system for detection, with an Ag / AgCl electrode as a reference electrode, a platinum wire electrode as a counter electrode, and a photoelectrochemical immunosensor as a working electrode, and test in 15 mL of a phosphate buffer solution with a pH of 5.0 to 8.0 containing collagen at a concentration of 0.05 to 0.25 mol / L;

[0056] Step 2: Use the time-current method to detect the collagen standard solution, set the running time to 50 s, the spectral range to 300-2500 nm, and the light intensity to 300 mW cm -2 , the distance between the light source and the electrode was fixed at 15 cm, and the open circuit voltage was used as the bias voltage;

[0057] Step 3: After the electrodes are placed, turn on the light every 20 seconds for 10 seconds, record the photocurrent, and draw a working curve;

[0058] Step 4: The cultural relic sample used is a leather cultural relic (a Qing Dynasty Mongolian dragon-patterned wood-carved painted rivet-covered drum) collected by the Inner Mongolia Museum. The collagen sample solution extracted from the leather cultural relic is used instead of the collagen standard solution for testing.

[0059] Comparative Example 1: The difference from Example 1 is that no AuNPs and Fe3O4 composite were added.

[0060] (1) Preparation of CdS: 1.8 g (CH3COO)2Cd and 1.2 g thiourea were added to 32 mL ethylenediamine and stirred for 0.5 h. After complete dissolution, the solution was transferred to a Teflon-lined stainless steel autoclave and heated at 180°C for 12 h. The obtained precipitate was dried at 40°C in vacuum overnight to obtain nanorod CdS.

[0061] (2) Preparation of Ab2-CdS: 0.2 g of nanorod CdS was ultrasonically dispersed in 0.5 mL of ultrapure water. Then, 0.5 mL of PBS solution (pH 7.4) containing Ab2 (8 mg / mL) and BSA (0.8 wt%) was added to the above solution. After 24 h at 4°C, an Ab2-CdS solution was obtained and stored at 4°C.

[0062] (6) Preparation of PEC immunosensor: 80 μL of Ab1 solution (8 g / mL) was dripped into a 96-well microplate and incubated for 0.5 h to allow Ab1 to adsorb on the surface of the microplate. Then, the unbound portion of Ab1 was removed and the microplate was washed twice with PBS buffer (pH 7.4). Subsequently, 1 wt %, 200 μL of BSA solution was added to the microplate to block nonspecific binding sites. After washing three times with PBS buffer (pH 7.4), 100 μL of collagen antigens with concentrations of 1 mg / mL, 1 μg / mL, 1 ng / mL, and 1 pg / mL were injected into the microplate, respectively. After standing for 0.5 h, it was washed three times with PBS buffer (pH 7.4). Finally, 80 μL of Ab2-CdS solution was dripped into the microplate to obtain an electrochemical immunosensor.

[0063] Comparative Example 2: The difference from Example 1 is that no Fe3O4 composite is added.

[0064] (1) Preparation of AuNPs: Take 100 μL of chloroauric acid solution, heat it to boiling, and then add 10 μL of sodium citrate. The concentration of the chloroauric acid solution is 0.8 mM, and the concentration of the sodium citrate solution is 0.08 mM. Stir for 10 min to obtain a wine-red Au NPs solution.

[0065] (2) Preparation of CdS: 1.8 g (CH3COO)2Cd and 1.2 g thiourea were added to 32 mL ethylenediamine and stirred for 0.5 h. After complete dissolution, the solution was transferred to a Teflon-lined stainless steel autoclave and heated at 180°C for 12 h. The obtained precipitate was dried at 40°C in vacuum overnight to obtain nanorod CdS.

[0066] (3) Preparation of Au / CdS: 0.5 g of nanorod CdS was dissolved in ultrapure water under ultrasound. After the solution was uniform, 30 mL of Au NPs solution was added and stirred for 10 h. After the reaction was complete, the solution was washed with ultrapure water and vacuum dried overnight to obtain Au / CdS nanocomposite materials.

[0067] (5) Preparation of Ab2-Au / CdS: 0.2 g of Au / CdS nanocomposite was ultrasonically dispersed in 0.5 mL of ultrapure water. Then, 0.5 mL of PBS solution (pH 7.4) containing Ab2 (8 mg / mL) and BSA (0.8 wt%) was added to the above solution. After 24 h at 4°C, an Ab2-Au / CdS solution was obtained, which was stored at 4°C.

[0068] (6) Preparation of PEC immunosensor: 80 μL of Ab1 solution (8 g / mL) was dripped into a 96-well microplate and incubated for 0.5 h to allow Ab1 to adsorb on the surface of the microplate. Then, the unbound portion of Ab1 was removed and the microplate was washed twice with PBS buffer (pH 7.4). Subsequently, 1 wt %, 200 μL of BSA solution was added to the microplate to block nonspecific binding sites. After washing three times with PBS buffer (pH 7.4), 100 μL of collagen antigens at concentrations of 1 mg / mL, 1 μg / mL, 1 ng / mL, and 1 pg / mL were injected into the microplate, respectively. After standing for 0.5 h, it was washed three times with PBS buffer (pH 7.4). Finally, 80 μL of Ab2-Au / CdS solution was dripped into the microplate to obtain an electrochemical immunosensor.

[0069] Comparative Example 3: The difference from Example 1 is that no AuNPs were added for compounding.

[0070] (1) Preparation of CdS: 1.8 g (CH3COO)2Cd and 1.2 g thiourea were added to 32 mL ethylenediamine and stirred for 0.5 h. After complete dissolution, the solution was transferred to a Teflon-lined stainless steel autoclave and heated at 180°C for 12 h. The obtained precipitate was dried at 40°C in vacuum overnight to obtain nanorod CdS.

[0071] (2) Preparation of CdS@Fe3O4: 0.2 g of nanorod CdS, 0.5 g of FeCl3·6H2O, 1.5 g of sodium acetate, 5 mL of ethylenediamine, and 10 mL of ethylene glycol were mixed under vigorous stirring. The mixture was transferred to a Teflon-lined stainless steel autoclave and heated at 180°C for 8 h. The obtained precipitate was vacuum dried at 40°C for 8 h to obtain CdS@Fe3O4 powder.

[0072] (3) Preparation of Ab2-CdS@Fe3O4: 0.2 g of CdS@Fe3O4 nanocomposite was ultrasonically dispersed in 0.5 mL of ultrapure water. Then, 0.5 mL of PBS solution (pH 7.4) containing Ab2 (8 mg / mL) and BSA (0.8 wt%) was added to the above solution. After 24 h at 4°C, Ab2-CdS@Fe3O4 solution was obtained and stored at 4°C.

[0073] (4) Preparation of PEC immunosensor: 80 μL of Ab1 solution (8 g / mL) was dripped into a 96-well microplate and incubated for 0.5 h to allow Ab1 to adsorb on the surface of the microplate. Then, the unbound portion of Ab1 was removed and the microplate was washed twice with PBS buffer (pH 7.4). Subsequently, 1 wt %, 200 μL of BSA solution was added to the microplate to block nonspecific binding sites. After washing three times with PBS buffer (pH 7.4), 100 μL of collagen antigens with concentrations of 1 mg / mL, 1 μg / mL, 1 ng / mL, and 1 pg / mL were injected into the microplate, respectively. After standing for 0.5 h, it was washed three times with PBS buffer (pH 7.4). Finally, 80 μL of Ab2-CdS@Fe3O4 solution was dripped into the microplate to obtain an electrochemical immunosensor.

[0074] Comparative Example 4: The difference from Example 1 is that AgNPs (Xianfeng Nano, CAS: 85-60-9, diameter: 20 nm, C: 0.1 mg / mL) are added to replace AuNPs.

[0075] (1) Preparation of CdS: 1.8 g (CH3COO)2Cd and 1.2 g thiourea were added to 32 mL ethylenediamine and stirred for 0.5 h. After complete dissolution, the solution was transferred to a Teflon-lined stainless steel autoclave and heated at 180°C for 12 h. The obtained precipitate was dried at 40°C in vacuum overnight to obtain nanorod CdS.

[0076] (2) Preparation of CdS@Fe3O4: 0.2 g of nanorod CdS, 0.5 g of FeCl3·6H2O, 1.5 g of sodium acetate, 5 mL of ethylenediamine, and 10 mL of ethylene glycol were mixed under vigorous stirring. The mixture was transferred to a Teflon-lined stainless steel autoclave and heated at 180°C for 8 h. The obtained precipitate was vacuum dried at 40°C for 8 h to obtain CdS@Fe3O4 powder.

[0077] (3) Preparation of Ag / CdS@Fe3O4: 0.5 g CdS@Fe3O4 was dissolved in ultrapure water under ultrasound. After the solution was uniform, 30 mL of 0.1 mg / mL Ag NPs solution was added and stirred for 10 h. After the reaction was complete, the solution was washed with ultrapure water and vacuum dried overnight to obtain Ag / CdS@Fe3O4 nanocomposite material.

[0078] (5) Preparation of Ab2-Ag / CdS@Fe3O4: 0.2 g of Ag / CdS@Fe3O4 nanocomposite was ultrasonically dispersed in 0.5 mL of ultrapure water. Then, 0.5 mL of PBS solution (pH 7.4) containing Ab2 (8 mg / mL) and BSA (0.8 wt%) was added to the above solution. After 24 h at 4°C, Ab2-Ag / CdS@Fe3O4 solution was obtained and stored at 4°C.

[0079] (6) Preparation of PEC immunosensor: 80 μL of Ab1 solution (8 g / mL) was dripped into a 96-well microplate and incubated for 0.5 h to allow Ab1 to adsorb on the surface of the microplate. Then, the unbound portion of Ab1 was removed and the microplate was washed twice with PBS buffer (pH 7.4). Subsequently, 1 wt % and 200 μL of BSA solution were added to the microplate to block nonspecific binding sites. After washing three times with PBS buffer (pH 7.4), 100 μL of collagen antigens with concentrations of 1 mg / mL, 1 μg / mL, 1 ng / mL, and 1 pg / mL were injected into the microplate, respectively. After standing for 0.5 h, the plate was washed three times with PBS buffer (pH 7.4). Finally, 80 μL of Ab2-Ag / CdS@Fe3O4 solution was dripped into the microplate to obtain an electrochemical immunosensor.

[0080] Comparative Example 5: The difference from Example 1 is that CdS and AuNPs are first compounded, and then Fe3O4 is added for compounding.

[0081] (1) Preparation of AuNPs: Take 100 μL of chloroauric acid solution, heat it to boiling, and then add 10 μL of sodium citrate (the concentration of chloroauric acid solution is 0.8 mM, and the concentration of sodium citrate is 0.08 mM). Stir for 10 min to obtain a wine-red AuNPs solution.

[0082] (2) Preparation of CdS: 1.8 g (CH3COO)2Cd and 1.2 g thiourea were added to 32 mL ethylenediamine and stirred for 0.5 h. After complete dissolution, the solution was transferred to a Teflon-lined stainless steel autoclave and heated at 180°C for 12 h. The obtained precipitate was dried at 40°C in vacuum overnight to obtain nanorod CdS.

[0083] (3) Preparation of Au / CdS: 0.5 g of nanorod CdS was dissolved in ultrapure water under ultrasound. After the solution was uniform, 30 mL of Au NPs solution was added and stirred for 10 h. After the reaction was complete, the solution was washed with ultrapure water and vacuum dried overnight to obtain Au / CdS nanocomposite materials.

[0084] (4) Preparation of Au / CdS@Fe3O4: 0.2 g Au / CdS nanocomposite, 0.5 g FeCl3·6H2O, 1.5 g sodium acetate, 5 mL ethylenediamine, and 10 mL ethylene glycol were mixed under vigorous stirring. The mixture was transferred to a Teflon-lined stainless steel autoclave and heated at 180°C for 8 h. The obtained precipitate was dried under vacuum at 40°C for 8 h to obtain Au / CdS@Fe3O4 nanocomposite.

[0085] (5) Preparation of Ab2-Au / CdS@Fe3O4: 0.2 g of Au / CdS@Fe3O4 nanocomposite was ultrasonically dispersed in 0.5 mL of ultrapure water. Then, 0.5 mL of PBS solution (pH 7.4) containing Ab2 (8 mg / mL) and BSA (0.8 wt%) was added to the above solution. After 24 h at 4°C, Ab2-Au / CdS@Fe3O4 solution was obtained and stored at 4°C.

[0086] (6) Preparation of PEC immunosensor: 80 μL of Ab1 solution (8 g / mL) was dripped into a 96-well microplate and incubated for 0.5 h to allow Ab1 to adsorb on the surface of the microplate. Then, the unbound portion of Ab1 was removed and the microplate was washed twice with PBS buffer (pH 7.4). Subsequently, 1 wt % and 200 μL of BSA solution were added to the microplate to block nonspecific binding sites. After washing three times with PBS buffer (pH 7.4), 100 μL of collagen antigens with concentrations of 1 mg / mL, 1 μg / mL, 1 ng / mL, and 1 pg / mL were injected into the microplate, respectively. After standing for 0.5 h, the plate was washed three times with PBS buffer (pH 7.4). Finally, 80 μL of Ab2-Au / CdS@Fe3O4 solution was dripped into the microplate to obtain an electrochemical immunosensor.

[0087] Table 1

[0088]

[0089] As shown in Table 1, the data indicate that the sensitivity of the immunosensor in Example 1 has been significantly improved, and both the heterojunction and noble metal plasma resonance strategies increase the absorption of visible light and the photocurrent, while the DPV peak response values ​​in Comparative Examples 1-3 have all decreased significantly.

[0090] Comparing Comparative Example 4 with Example 1, compared with other metal nanoparticles, Au NPs have better biocompatibility, and Au NPs have good conductivity, large specific surface area and ability to fix antibodies. The experimental results also show that adding Au NPs to the composite can make the material's response to photocurrent stronger.

[0091] Comparison between Comparative Example 5 and Example 1 shows that the photocurrent can be improved by first forming a heterojunction of CdS@Fe3O4, while when CdS and AuNPs are first compounded and then Fe3O4 is added to compound, the heterostructure of CdS@Fe3O4 will be destroyed, thereby changing the response value of the composite material to the photocurrent.

[0092] The above embodiments of the present invention are merely examples for illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes and modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for preparing an electrochemical immunosensor for leather cultural relics detection, characterized in that: The steps include: (1) Preparation of CdS@Fe3O4: Nanorod-shaped CdS was mixed with FeCl3·6H2O, sodium acetate, ethylenediamine and ethylene glycol; the mixture was heated in a reactor for reaction, cooled naturally to room temperature, filtered, washed and vacuum dried to obtain a CdS@Fe3O4 nanocomposite material; (2) Preparation of Au / CdS@Fe3O4: CdS@Fe3O4 nanocomposite material was dissolved in ultrapure water under ultrasonic wave, Au NPs solution was added and stirred, and then filtered, washed and vacuum dried to obtain Au / CdS@Fe3O4 nanocomposite material; (3) Preparation of Ab2-Au / CdS@Fe3O4: The Au / CdS@Fe3O4 nanocomposite was ultrasonically dispersed in ultrapure water, and a PBS solution containing Ab2 and BSA was added. After incubation, the Ab2-Au / CdS@Fe3O4 solution was obtained and stored at 4°C. (4) Preparation of PEC immunosensor: drop Ab1 solution into the microplate, incubate, and wash the microplate with PBS buffer; drop BSA solution into the microplate and wash with PBS buffer; The collagen antigen was dropped into the microplate and washed with PBS buffer; finally, the Ab2- Au / CdS@Fe3O4 solution was dropped into the microplate to obtain an electrochemical immunosensor.

2. The method for preparing the electrochemical immunosensor for leather cultural relics detection according to claim 1, characterized in that: Preparation of nanorod-shaped CdS in step (1): The nanorod-shaped CdS is prepared by a water bath method, wherein (CH3COO)2Cd and thiourea are added to ethylenediamine, stirred until completely dissolved, heated in a reactor for reaction, cooled, washed, and vacuum dried to obtain nanorod-shaped CdS.

3. The method for preparing the electrochemical immunosensor for leather cultural relics detection as claimed in claim 2, characterized in that: The ratio of the added amounts of (CH3COO)2Cd, thiourea and ethylenediamine is 1.8-2.0 g: 1.2-1.5 g: 32 mL; the stirring time is 0.5-1 h; the heating reaction is transferring the solution to a reaction kettle and heating at 180-200°C for 12-24 h; the vacuum drying temperature is 40-60°C.

4. The method for preparing the electrochemical immunosensor for leather cultural relics detection according to claim 1, characterized in that: In step (1), the mixing ratio of nanorod-shaped CdS, FeCl3·6H2O, sodium acetate, ethylenediamine and ethylene glycol is 0.2-0.4 g: 0.5-0.8 g: 1.5-1.8 g: 5-7 mL: 10-12 mL; the mass ratio of nanorod-shaped CdS to FeCl3·6H2O is 1:1-3; the heating reaction in the reactor is to transfer the mixture to the reactor and heat it at 180-200°C for 8-12h.

5. The method for preparing the electrochemical immunosensor for leather cultural relics detection according to any one of claims 1 to 4, characterized in that: Preparation of Au NPs in step (2): Heat the chloroauric acid solution to a boil, then drop a sodium citrate solution into the solution and stir evenly to obtain an Au NPs solution.

6. The method for preparing the electrochemical immunosensor for leather cultural relics detection according to claim 5, characterized in that: The concentration of the chloroauric acid solution is 0.8-1.2 mM; the concentration of the sodium citrate solution is 0.08-0.12 mM; and the stirring time is 10-20 min.

7. The method for preparing the electrochemical immunosensor for leather cultural relics detection according to claim 1, characterized in that: In step (2), the mixing ratio of CdS@Fe3O4 nanocomposite material and Au NPs solution is 0.5 - 0.8 g: 30 - 50 mL; and the stirring time is 10 - 12 h.

8. The method for preparing the electrochemical immunosensor for leather cultural relics detection according to claim 1 or 7, characterized in that: In step (3), the mixing ratio of Au / CdS@Fe3O4 nanocomposite material, ultrapure water and PBS solution containing Ab2 and BSA is 0.2 - 0.3 g: 0.5 - 0.6 mL: 0.5 - 0.8 mL; in the PBS solution containing Ab2 and BSA, the concentration of Ab2 is 8-10 mg / mL, and the concentration of BSA is 0.8-1 wt%; the incubation is at 4°C for 24-30h.

9. The method for preparing the electrochemical immunosensor for leather cultural relics detection according to claim 1 or 7, characterized in that: In step (4), the volume ratio of Ab1 solution, BSA solution, collagen antigen solution, and Ab2-Au / CdS@Fe3O4 solution is 80-100:200:100:80-100; the concentration of Ab1 solution is 8-10 g / mL, and the incubation time is 0.5-1 h; the concentration of BSA solution is 1-3 wt%.

10. Use of the electrochemical immunosensor prepared by the preparation method according to any one of claims 1 to 9 in the detection of leather cultural relics.

Citation Information

Patent Citations

  • In-vitro sandwich immunoassay process with magnetic separation for detecting alpha fetoprotein

    CN102879582A

  • Preparation method and use of CdS-Fe3O4-based electrochemiluminescence sensor

    CN104316707A

  • Preparation method of photoelectrochemical immunosensor for detecting collagen

    CN112858438A

  • Method for detecting leather textile cultural relics based on colorimetric analysis

    CN116466094A

  • Kit for detecting collagen functional domain based on receptor as well as preparation and application of kit

    CN117451999A